Changing Definitions of Sepsis - (:unkn) unknown (AVES, 2017)
Sepsis is one of the main causes of morbidity and mortality in critically ill patients despite the use of modern antibiotics and resuscitation therapies. Outcomes in sepsis have improved overall, probably because of an enhanced focus on early diagnosis and other improvements in supportive care, but mortality rates still remain unacceptably high. The diagnosis and definition of sepsis is a critical problem due to the heterogeneity of this disease process. Although it is apparent that much more needs to be done to advance our understanding, sepsis and related terms remain difficult to define. A 1991 consensus conference developed initial definitions that systemic inflammatory response syndrome (SIRS) to infection would be called sepsis. Definitions of sepsis and septic shock were revised in 2001 to incorporate the threshold values for organ damage. In early 2016, the new definitions of sepsis and septic shock have changed dramatically. Sepsis is now defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. The consensus document describes organ dysfunction as an acute increase in total Sequential Organ Failure Assessment ( SOFA) score two points consequently to the infection. A significant change in the new definitions is the elimination of any mention of SIRS. The Sepsis-3 Task Force also introduced a new bedside index, called the qSOFA, to identify outside of critical care units patients with suspected infection who are likely to develop sepsis. Recently updated the consensus definitions improved specificity compared with the previous descriptions.
Keywords: Sepsis; definitions; septic shock; SIRS; INTERNATIONAL CONSENSUS DEFINITIONS; TIDAL CARBON-DIOXIDE; SURVIVING SEPSIS; NATIONWIDE TRENDS; SOFA SCORE; CRITERIA; MORTALITY; IMMUNOSUPPRESSION; GUIDELINES; INFECTION